GAMBARAN KUALITAS HIDUP PEKERJA DI SEKTOR PARIWISATA WILAYAH BALI SELATAN - Ida Ayu Karina Adityanti Manuaba; Ni Made Gandhi Sanjiwani; Ni Kadek Anggun Dwi Lestari (unprimdn.ac.id, 2023)
The province of Bali is inseparable from tourism. Tourism influences life satisfaction. Overall life satisfaction is derived from satisfaction with aspects of life such as material well-being, social well-being, emotional well-being, and health and safety well-being. These dimensions lead to quality of life, so the community's quality of life must be the government's and other stakeholders' primary concern. South Bali is one of the strategic tourism areas in Bali Province, so the readiness and support of the local community are critical. This research focuses on people who work in the tourism sector in the South Bali Region. The researcher emphasizes tourism-affiliated communities, which may be more sensitive to the impacts of tourism. The purpose of this study is to determine workers' perceptions regarding tourism's impact on their quality of life. This study used a descriptive quantitative approach with a questionnaire as a data collection tool. The results showed that, in general, workers' quality of life was in the moderate category, which amounted to 38.58% of 127 respondents. This data can be a reference for stakeholders or other stakeholders in paying attention to each indicator so that workers in the tourism sector who also reside or become communities in the South Bali Region can obtain life satisfaction as a result of the tourism industry in the region.